2017
DOI: 10.1111/hel.12412
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer: Basic aspects

Abstract: Gastric cancer is one of the most incident and deadliest malignancies in the world. Gastric cancer is a heterogeneous disease and the end point of a long and multistep process, which results from the stepwise accumulation of numerous (epi)genetic alterations, leading to dysregulation of oncogenic and tumor suppressor pathways. Gastric cancer stem cells have emerged as fundamental players in cancer development and as contributors to gastric cancer heterogeneity. For this special issue, we will report last year'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…Additionally, it has been found that the incidence of GC is twice as high in men than in women, implying that hormonal differences may also be risk factors for GC progression [ 10 , 11 ]. In recent years, with the development of enteroscopy and surgical techniques, the five-year overall survival rate for early-stage GC patients has significantly improved, but for advanced-stage GC patients, the five-year survival rate is still unsatisfactory at <25% [ 12 , 13 ]. The high mortality of GC is mainly attributed to delayed diagnosis due to the absence of screening programs; the lack of desirable molecular biomarkers and the paucity of specific early clinical symptoms; and the common forms of recurrence, including peritoneal dissemination, hematogenous spread, and lymph node metastasis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been found that the incidence of GC is twice as high in men than in women, implying that hormonal differences may also be risk factors for GC progression [ 10 , 11 ]. In recent years, with the development of enteroscopy and surgical techniques, the five-year overall survival rate for early-stage GC patients has significantly improved, but for advanced-stage GC patients, the five-year survival rate is still unsatisfactory at <25% [ 12 , 13 ]. The high mortality of GC is mainly attributed to delayed diagnosis due to the absence of screening programs; the lack of desirable molecular biomarkers and the paucity of specific early clinical symptoms; and the common forms of recurrence, including peritoneal dissemination, hematogenous spread, and lymph node metastasis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that EpCAM(+)/CD44(+) cells grow exponentially in vitro as cancer spheres in SFM [25]. Furthermore, pluripotent stem cell factors like Oct4, Sox2 and Nanog also regulate GCSCs properties [13,26]. In the present study, we showed signi cantly elevated tumorsphere formation capacity of both BGC-823 and SGC-7901 cells cultured in SFM, as well as markedly increased expression levels of GCSCs markers in the sphere-forming cells, which depicted the enrichment of GCSCs.…”
Section: Discussionmentioning
confidence: 99%
“…GCSCs were rst described in 2007 by Yang et al [12]. Accumulating evidence indicates that GCSCs are the root of gastric cancer development and progression [13][14][15][16][17]. Moreover, chemotherapy has been found to induce cancer cell stemness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of gastric cancer has decreased in recent years (1,2), it remains the third leading cause of cancer-associated mortality worldwide, with ~1,000,000 new cases diagnosed each year (3,4). Improved techniques for the treatment of gastric cancer have been developed, including novel surgical methods, radiation and chemotherapy protocols; however, the prognoses of patients with advanced gastric cancer remain poor, with a 5-year survival of 5–20% (5,6).…”
Section: Introductionmentioning
confidence: 99%